2015
DOI: 10.7150/jca.12191
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling Identifies Bezafibrate as Potential Therapeutic Drug for Lung Adenocarcinoma

Abstract: Drug-induced gene expression patterns that invert disease profiles have recently been illustrated to be a new strategy for drug-repositioning. In the present study, we validated this approach and focused on prediction of novel drugs for lung adenocarcinoma (AC), for which there is a pressing need to find novel therapeutic compounds. Firstly, connectivity map (CMap) analysis computationally predicted bezafibrate as a putative compound against lung AC. Then this hypothesis was verified by in vitro assays of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…A few previous studies have used gene set enrichment analysis to connect disease signatures with drug signatures and identified candidate drugs for cancer, neurological, and gastrointestinal disorders, as suggested by subsequent effect studies in cell lines and animal models (3)(4)(5)(6). However, it remains to be shown whether such signature connections can be used to identify compounds with pathophysiological relevance for humans.…”
Section: Introductionmentioning
confidence: 99%
“…A few previous studies have used gene set enrichment analysis to connect disease signatures with drug signatures and identified candidate drugs for cancer, neurological, and gastrointestinal disorders, as suggested by subsequent effect studies in cell lines and animal models (3)(4)(5)(6). However, it remains to be shown whether such signature connections can be used to identify compounds with pathophysiological relevance for humans.…”
Section: Introductionmentioning
confidence: 99%
“…Bezafibrate, as an agonist of PGC-1α/PPAR complexes, has showed synergistic tumor-suppression activity with anti-PD-L1 monoclonal antibody (mAb) in mouse colon xenograft models. 8,9 However, although Liu et al 10 has found bezafibrate may be a potential therapeutic drug for lung adenocarcinoma (AC) by targeting cyclin-dependent kinase 2 (CDK2) to induce cell cycle arrest in lung (AC) cells, there is rare report of bezafibrate in regulating the function of T cells, let alone enhancing the antitumor effect of PD-1 blockade in lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the prognosis of patients with glioma, we used CMap to obtain four small molecule compounds with potential therapeutic effects on glioma. Recently, a study uncovered that beza brate can serves as a drug for lung adenocarcinoma in vitro assays, in which inhibited proliferation and caused cell cycle arrest [37]. Giacinti et al revealed that scriptaid has strong antitumour activity in breast cancer cell lines [38].…”
Section: Discussionmentioning
confidence: 99%